2021
DOI: 10.1001/jamanetworkopen.2021.22277
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dietary Patterns and All-Cause Mortality

Abstract: IMPORTANCE The 2020 Dietary Guidelines Advisory Committee conducted a systematic review of existing research on diet and health to inform the current Dietary Guidelines for Americans. The committee answered this public health question: what is the association between dietary patterns consumed and all-cause mortality (ACM)? OBJECTIVE To ascertain the association between dietary patterns consumed and ACM. EVIDENCE REVIEW Guided by an analytical framework and predefined inclusion and exclusion criteria developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 173 publications
(963 reference statements)
0
92
0
1
Order By: Relevance
“…Globally, more than half of the deaths annually are due to CVDs and cancers [ 39 ]. A healthy diet plays a profound role in these conditions [ 40 ]. UPFs, food, and drink products that have undergone specified types of food processing have been shown to markedly increase the risk of mortality in many countries [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, more than half of the deaths annually are due to CVDs and cancers [ 39 ]. A healthy diet plays a profound role in these conditions [ 40 ]. UPFs, food, and drink products that have undergone specified types of food processing have been shown to markedly increase the risk of mortality in many countries [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a systemic review, a total of 1 randomized clinical trial and 152 observational studies were included comprising of adults and older adults, aged 17-84 years from 28 countries with high or very high Human Development Index [19]. The findings suggested that dietary patterns (possibly rich in flavonoids), including higher intake of vegetables, fruits, legumes, nuts, whole grains, unsaturated vegetable oils, fish, and lean meat or poultry, were associated with a decreased risk of all-cause mortality.…”
Section: Foods Requiring Masticationmentioning
confidence: 99%
“…To account for the overall diet quality, we defined a healthy diet score based on the following diet factors: vegetable intake (< median = 0 and ≥ median = 1), fruit intake (< median = 0 and ≥ median = 1), unprocessed red meat intake (< median = 1 and ≥ median = 0), and fish intake (< median = 0 and ≥ median = 1) [27]. These diet factors consider several common components of a priori healthy eating patterns [28]; thus, it could roughly reflect the overall diet quality [27]. The healthy diet score ranged from 0 to 4.…”
Section: Dietary Assessment and Upf Intakementioning
confidence: 99%